America's first Olympics the St. Louis games of 1904 - Matthews, George R., 1950-; ebrary, Inc. (Columbia : University of Missouri Press, 2005)
"Explores the history of the 1904 Olympics, held in St. Louis, Missouri, which featured first-time African American Olympians, a controversial marathon, and documentation by photojournalist Jessie Tarbox Beals. Examines the controversy surrounding the transfer of the games from Chicago to St. Louis"--Provided by publisher.
A tale of two cities -- The ghost of Plato -- Transfer accepted -- St. Louis Olympian games -- Place in history.
Includes bibliographical references (p. 223-229) and index.
Electronic reproduction.
Keywords: Electronic books